Pengaruh Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Provis Garuda Service Di Pelabuhan Bakauheni Lampung Selatan - Pramana Putra, Nanda; Herawati, Heny (LPPM STIE KRAKATAU, 2017)
This research is eksploratif. This research is intended to make the exposure study systematically,factual, and accurate information on the facts - the facts and the nature - the nature of a particularpopulation. This study used 95 study respondents. There are three variables in this study are: two (2)independent variables (X1 and X2) and 1 (one) in which the dependent variable Leadership (X1) andWork environment (X2) as independent variables and Employee Performance (Y) as variable bound.From the data processing has been found that answers the following hypothesis; there is Leadershipinfluence (X1) on Employee Performance (Y), with the degree of influence (R-square) of 28.9%,.There is the influence of Work environment (X2) toward Employee Performance (Y), with the degreeof influence of 28.3%. There is the influence of leadership (X1) and work environment (X2) bysimultans toward Employee Performance (Y), with the degree of influence of 29.6%.